Structural Diversity and Anticancer Activity of Marine‐Derived Elastase Inhibitors: Key Features and Mechanisms Mediating the Antimetastatic Effects in Invasive Breast Cancer. (23rd March 2018) - Al‐Awadhi, Fatma H.; Paul, Valerie J.; Luesch, Hendrik
Abstract: Three new 3‐amino‐6‐hydroxy‐2‐piperidone (Ahp)‐containing cyclic depsipeptides, named loggerpeptins A–C (1 – 3 ), along with molassamide (4 ), were discovered from a marine cyanobacterium, extending the structural diversity of this prevalent scaffold of cyanobacterial serine protease inhibitors. Molassamide, which contains a 2‐amino‐butenoic (Abu) unit in the cyclic core, was the most potent and selective analogue against human neutrophil elastase (HNE). Given the growing evidence supporting the role of HNE in breast cancer progression and metastasis, we assessed the cellular effects of compounds3 and4 in the context of targeting invasive breast cancer. Both compounds inhibited cleavage of the elastase substrate CD40 in biochemical assays; however, only4 exhibited significant cellular activity. As CD40 and other receptor proteolytic processing culminates in NFκB activation, we assessed the effects of4 on the expression of target genes, including ICAM‐1 . ICAM‐1 is also a direct target of elastase and, in our studies, compound4 attenuated both elastase‐induced ICAM‐1 gene expression and ICAM‐1 proteolytic processing by elastase, revealing a potential dual effect on migration through modulation of gene expression and proteolytic processing. Molassamide also specifically inhibited the elastase‐mediated migration of highly invasive triple ‐ negative breast cancer cells. Abstract : Cyanobacteria against cancer : Chemical exploration of a marine cyanobacterium led to the discovery of three new elastase inhibitors, loggerpeptins A–C, along with molassamide, that might be valuable for anticancer therapeutics. Molassamide was the most potent analogue and inhibited cleavage of CD40 and expression and cleavage of downstream target ICAM‐1, as well as elastase‐induced migration of invasive breast cancer cells.